Análise da interface de união entre cimento resinoso auto-adesivo à dentina erodida in vitro - Moda, Mariana Dias [UNESP] (2016)
Considering the significant increase of erosive lesions and the need for studies to evaluate the adhesion on a eroded substrate. The purpose of this study was to evaluate the bonding interface between self-adhesive resin cement to in vitro eroded dentin. Seventy-two third molars were used and divided into two groups: group 1 (sound dentin) and group 2 (eroded dentin). The in vitro erosion was created following a demineralization protocol, in which the specimens of group 2 were immersed in demineralizing solutions 2 minutes per cycle, and in remineralizing solution, 10 minutes per cycle, during 9 days. Both groups were submitted to four dentin surface treatments: control group (without any treatment), 2% chlorhexidine, 20% polyacrylic acid, and 0,1M EDTA pH 7.4 (n=9). TPH resin-based composite blocks were bonded with RelyX U200 self-adhesive resin cement on the pretreated dentin surfaces. The teeth were submitted to precision cutter, thus obtaining samples forms of sticks. The samples were submitted to microtensile bonding test to evaluate the bonding strength between selfadhesive resin cement to dentin, 24 hours and 8 months after the bonding procedure. The fractured samples were evaluated in scanning electron microscopy (SEM), to classify the fracture pattern of these interfaces. Finally, three specimens of each group were longitudinal cut and obtained three slices per group and evaluating by confocal laser scanning microscopy (CLSM), with the purpose to analyze qualitatively the dentin/cement interface. The results showed that the etched dentin showed significant increase in density and depth of resinous tags compared to sound dentin, although little difference in bond strength values has been found. Different types of treatments performed on dentin, in general, increased the bonding strength values compared to the control group. The storage of the samples in artificial saliva for 8 months, seems to have been not enough to cause significant degradation of the adhesive interface.